THE PREVALENCE OF EYE INVOLVEMENTS IN RHEUMATOID ARTHRITIS AND THEIR CORRELATION WITH ANTI-CYCLIC CITRULLINATED PEPTIDE ANTIBODY IN SULAIMANI GOVERNORATE/IRAQ - Mustafa, Rawand Ali; Mirza, Raouf Rahim; Rasool, Hemn Raof (Journal of Sulaimani Medical College, 2025)
Background Rheumatoid arthritis is a common autoinflammatory disease that affects the joints and causes several extraarticular problems, including ocular involvement, which typically manifests in the anterior ocular region. The anti-CCP has a sensitivity comparable to the rheumatoid factor and higher specificity for identifying the disease. Objectives To estimate the prevalence of eye involvements in Rheumatoid arthritis and their correlation to the anti-cyclic citrullinated peptide antibody. Patients and Methods A cross-sectional study of 121 patients who satisfied the 2010 ACR/EULAR RA Classification Criteria (6/10 or more points) were between 18 and 60. After establishing a patient’s medical history and physical examination, blood samples were collected to test for anti-CCP antibodies, and an eye exam was conducted. Results There were significantly more females than males;104 (86%) were female, and 17 (14%) were males. The median age was 47(42−53.5) years. The median disease duration was 4(2−10) years. The mean disease activity was 3.86 ±1, and the median anti-cyclic citrullinated antibody titers were 29.18(16.75−133.35) U/ml. The overall eye complications typical of Rheumatoid arthritis were observed in 37 (30.6%) and 84 (69.4%) without eye involvement. Dry eyes were the most frequent eye complaint (29.8%). One instance with episcleritis (0.8%). One with filamentary keratitis (0.8%). Anterior uveitis was detected in two cases (1.7%). Eye involvement correlated with anti-cyclic citrullinated peptide antibody (P- value 0.004). Conclusion Eye manifestations of rheumatoid arthritis were a prominent part of extra-articular manifestation. The dry eye was the most apparent manifestation, and they correlated to the anti-CCP antibody.
Keywords: Rheumatoid Arthritis; Episcleritis; antiCCP antibody; ocular manifestation; dry eye